IDENTIFICATION OF DROUGHT DISTRIBUTION BASED ON SOIL MOISTURE INDEX (SMI) AND STANDARDIZED PRECIPITATION INDEX (SPI) METHODS IN WEST JAVA - Diryatika, Esy
Mapping the spread of drought can not only be identified using rainfall parameters, but can also be seen by considering soil moisture data. The Soil Moisture Index (SMI) is a drought index that relies on soil moisture parameters. There is potential for the SMI index to be used for drought detection in West Java. Therefore, this study aims to identify the distribution of drought using the SMI index by comparing it to the Standardized Precipitation Index (SPI), which has been commonly used and proven to be accurate. In this study, drought identification was carried out using the SMI method with the input of ERA5 Land soil moisture data and SPI with CHIRPS rainfall data input. Additionally, this study also conducted a correlation test on the results of the two indexes to see the relationship between the results of the two indexes. The drought distribution detected using the SMI and SPI method shows the same drought pattern. However, the drought intensity generated by the SMI tends to be higher than the SPI. This can be seen from the results of the drought distribution plots of the two indices, both temporally and spatially. Additionally, based on the correlation of the two indices, derived from the average drought value of all regions every year. The highest correlation occurs with a time lag of 1 month and a value of 0.67. This indicates that the impact of meteorological drought (SPI) on agricultural drought (SMI) has a one-month lag.